Ammonium oxidation by bacteria and archaea have functional implications for nitrification across a forested landscape - Jennifer Wen; Rima Upchurch; Donald R. Zak (Ecosphere)
Abstract Ammonia‐oxidizing archaea (AOA) and ammonia‐oxidizing bacteria (AOB) control nitrification in terrestrial systems. Soil pH and substrate availability (NH4+) can influence community composition, which may affect the contributions of these organisms to nitrification in forest soils. Using high‐throughput sequencing, we identified the amoA of AOA and AOB from northern forest stands that occur across a natural gradient of nitrification, soil pH, and net N mineralization (i.e., NH4+ availability). Specifically, we investigated changes in relative abundance and community composition of AOA and AOB across a soil pH and net N mineralization gradient, and how turnover in community composition is linked to nitrification. We found that soil pH was a stronger driver of AOA and AOB relative abundance than was NH4+ availability. Generally, AOA and AOB turnover were positively associated with soil pH; however, some AOA taxa also displayed a negative association. Interestingly, the relative abundance of only a small number of AOA and AOB taxa was significantly associated with net nitrification rates. Our findings reveal that coexisting taxonomical groups of ammonia‐oxidizers in forest soils have diverse responses to environmental factors, which influence how ammonia‐oxidizer communities are structured, likely having direct implications for nitrification and the regulation of N cycling in forest systems.